Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)2/9-(-4/9)=6/9=2/3
b)(-1/24+0,25+1 1/12):(-1/2)2
=(-1/24+6/24+26/24):(-1/2).2
=31/24.-2.2
=-31/12.2
=-31/6
c)3/13.(-5/9)+10/13.(-5/9)+(-4/9)
=-5/9(3/13+10/13)+(-4/9)
=-5/9.1+(-4/9)
=-1
a,10x+65=125
10x =125-65
x =60:10
x =6
Vậy:...
b,45-(5-2x)^3=2.3^2
45-(5-2x)^3=18
(5-2x)^3 =45-18
(5-2x)^3 =27=3^3
=> 5-2x = 3
2x = 5-3
x= 2:2
x=1
Vậy:....
-Hok tốt ~ K mk nhak.
a, 10x + 65 = 125
10x = 125 - 65
10x = 60
x = 60 : 10
x = 6
b,45-(5-2x)^3=2.3^2
45 - ( 5 - 2x )^3 =18
(5 - 2x)^3 = 45 - 18
(5 - 2x )^3= 3^3
5 - 2x = 3
2x = 2
x = 1
c,2(x-3)-12=(-10)
2x - 6 -12 =-10
2x = -10 + 6 + 12
2x = 8
x = 4
d,x-12=(-13)+1+|-13|
x - 12 = -13 + 1 + 13
x - 12 = 1
x = 13
hok tốt!!!
a; - \(\dfrac{10}{13}\) + \(\dfrac{5}{17}\) - \(\dfrac{3}{13}\) + \(\dfrac{12}{17}\) - \(\dfrac{11}{20}\)
= - (\(\dfrac{10}{13}\) + \(\dfrac{3}{13}\)) + (\(\dfrac{5}{17}\) + \(\dfrac{12}{17}\)) - \(\dfrac{11}{20}\)
= - 1 + 1 - \(\dfrac{11}{20}\)
= 0 - \(\dfrac{11}{20}\)
= - \(\dfrac{11}{20}\)
b; \(\dfrac{3}{4}\) + \(\dfrac{-5}{6}\) - \(\dfrac{11}{-12}\)
= \(\dfrac{9}{12}\) - \(\dfrac{10}{12}\) + \(\dfrac{11}{12}\)
= \(\dfrac{10}{12}\)
= \(\dfrac{5}{6}\)
c; [13.\(\dfrac{4}{9}\) + 2.\(\dfrac{1}{9}\)] - 3.\(\dfrac{4}{9}\)
= [\(\dfrac{52}{9}\) + \(\dfrac{2}{9}\)] - \(\dfrac{4}{3}\)
= \(\dfrac{54}{9}\) - \(\dfrac{4}{3}\)
= \(\dfrac{14}{3}\)
Bài 2 : Tính
1/ (-15)-/-10/+/-9/-/-5/
=-15-10+9-5
=-21
2/14-(-13)-(-21)+(-32)
=14+13+21-32
=16
3/(-12)-(-17)-(-21)+(-32)
= -12+17+21-32
=-6
4/-/-14/ + /-10/-(-12)+(-8)
=-14+10+12-8
=0
5/-(-11)+(-15)+(+13)-21
=11-15+13-21
=-12
a) \(\left(x+\frac{1}{4}-\frac{1}{3}\right):\left(2+\frac{1}{6}-\frac{1}{4}\right)=\frac{7}{46}\)
\(\left(x-\frac{1}{12}\right):\left(2-\frac{1}{12}\right)=\frac{7}{46}\)
\(\left(x-\frac{1}{12}\right):\frac{23}{12}=\frac{7}{46}\)
\(x-\frac{1}{12}=\frac{7}{46}.\frac{23}{12}\)
\(x-\frac{1}{12}=\frac{7}{24}\)
\(x=\frac{7}{24}+\frac{1}{12}\)
\(x=\frac{3}{8}\)
Vậy \(x=\frac{3}{8}\)
b) \(\frac{13}{15}-\left(\frac{13}{21}+x\right).\frac{7}{12}=\frac{7}{10}\)
\(\frac{13}{15}-\left(\frac{13}{21}+x\right)=\frac{7}{10}:\frac{7}{12}\)
\(\frac{13}{15}-\left(\frac{13}{21}+x\right)=\frac{7}{10}.\frac{12}{7}\)
\(\frac{13}{15}-\left(\frac{13}{21}+x\right)=\frac{6}{5}\)
\(\frac{13}{21}+x=\frac{13}{15}-\frac{6}{5}\)
\(\frac{13}{21}+x=\frac{-1}{3}\)
\(x=\frac{-1}{3}-\frac{13}{21}\)
\(x=\frac{-20}{21}\)
Vậy \(x=\frac{-20}{21}\)
a, x : 46 / 15 = 13 / 12
x = 13/12 . 46/15
x = 299/90
b, - 2/3x + 1 / 5 = 3 / 10
- 2 / 3 x = 3 / 10 - 1 / 5
- 2 / 3 x = 1 / 10
x = -3 / 20
c, x : 13 / 3 = - 2 / 5
x = - 2 / 5 . 13 / 3
x = -26 /15
d, 2 / 4 x + 2 / 5 x = 1
x ( 2 / 4 + 2 / 5 ) = 1
x . 9 / 10 = 1
x = 10 / 9
a) \(2\left(x-3\right)-12=-10\)
\(\Leftrightarrow2x-6=2\)
\(\Leftrightarrow x=4\)
b) \(x-12=-13+1+\left|-13\right|\)
\(\Leftrightarrow x-12=-13+1+13\)
\(\Leftrightarrow x-12=1\)
\(\Leftrightarrow x=13\)
a. 2 ( x - 3 ) - 12 = - 10
=> 2 ( x - 3 ) = 2
=> x - 3 = 1
=> x = 4
b. x - 12 = ( - 13 ) + 1 + | - 13 |
=> x - 12 = - 13 + 13 + 1
=> x - 12 = 1
=> x = 13